FAVREINA CARPATICA N. ICHNOSP. (CRUSTACEAN MICROCOPROLITE) FROM THE MIDDLE JURASSIC OF RUCĂR-BRAN ZONE (SOUTHERN CARPATHIANS, ROMANIA) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2013)
The new crustacean microcoprolite, Favreina  carpatica ,is described from the Middle Jurassic of Rucăr-Bran zone, South Carpathians. It is the ichnospecies with the highest number (about 280) of longitudinally arranged canals pasing through the rod-shaped microcoprolite. Favreina carpatica was found in reddish to brown-carbonate sediments.
Keywords: Crustacean; microcoprolite; Favreina; Middle Jurassic; Southern Carpathians; Rucăr-Bran zone